2010
DOI: 10.1308/003588410x12699663904998
|View full text |Cite
|
Sign up to set email alerts
|

Erect chest radiography in the setting of the acute abdomen: essential tool or an unnecessary waste of resources?

Abstract: Ann R Coll Surg Engl 2010; 92: 697-699 697Patients admitted as an emergency with abdominal pain often undergo two standard imaging studies in the acute setting, namely an erect chest and supine abdominal radiograph. The indications for the erect chest radiograph (CXR) are first to exclude free gas under the diaphragm as a result of a perforated viscus, and second to attempt to exclude an intrathoracic condition as a cause for the abdominal symptoms.The Royal College of Radiologists (RCR) recommends a CXR be pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…One study trying to assess if a chest X-ray should be ordered for every patient complaining of abdominal pain, ordered a chest radiograph on all patients admitted to the surgical ward (344 patients) for abdominal pain. The results revealed that 7% had a new finding and 1% had air under the diaphragm, respectively [20]. As a result, the vast majority of the X-rays that were requested were normal.…”
Section: Discussionmentioning
confidence: 97%
“…One study trying to assess if a chest X-ray should be ordered for every patient complaining of abdominal pain, ordered a chest radiograph on all patients admitted to the surgical ward (344 patients) for abdominal pain. The results revealed that 7% had a new finding and 1% had air under the diaphragm, respectively [20]. As a result, the vast majority of the X-rays that were requested were normal.…”
Section: Discussionmentioning
confidence: 97%
“…3 Considering the radiation exposure and waste of resources, it has been recently recommended that chest X-ray performed on patients admitted with acute abdominal pain are mostly unnecessary. 9 However, several cardiopulmonary indications in children can certainly mimic primary abdominal diseases, ranging from the mostly seen pneumonia, pleuritis, myocarditis, and pericarditis, to the lesser seen acute mediastinitis, aortitis, and spontaneous rupture of the esophagus. 1,10 In particular lungs and pleura are important parts of RUQ and always need to be considered in RUQ pain.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies have reported its sensitivity for detecting free gas in the presence of hollow viscus perforation. 1- 4 We excluded the many other studies in this area that combined multiple plain film techniques (for example, abdominal, supine, or lateral decubitus films) or looked at iatrogenic pneumoperitoneum from our analysis (table⇓). [5][6][7][8] The level of evidence put forward by these studies varied greatly, with cohort sizes ranging from seven to 94 and reported sensitivities of 40-85% (table).…”
Section: Long Answermentioning
confidence: 99%